Auditoría de gestión al componente de talento humano del Distrito de Salud 11D01-Z7, Centro de Salud número uno, de la ciudad de Loja, período 2017 - Capa Valle, Miriam Jhuliana (2018)
The present thesis work of Management Audit to the Human Talent Component in the Health District 11D01Z, Health Center Nº1, Period 2017, was carried out with the purpose of evaluating the development of the activities within the perspective of ethics, efficiency, effectiveness and quality and propose recommendations that lead to improving the institutional management in regard to its Human Talent component. It began with the preliminary knowledge phase, where the visit to the entity was made, which allowed to know the way and when to perform the internal control assessment, they were established; the scope of work, the program and detailed procedures to follow in the development of the work; in the execution of the audit work, sufficient information was obtained and through the SWOT analysis, the application of substantive and compliance tests was determined; Likewise, management indicators were applied to obtain conclusions related to the objectives of the audit, then the working papers were prepared with the information obtained; in the communication of results, the report was prepared with the appropriate conclusions and recommendations and finally the follow-up where a schedule is established based on the recommendations. In the development of the management audit, a methodology was applied in each of the phases of the same, in addition techniques such as interview, observation, verification and surveys were applied, which served to obtain the results presented.